Differential spatial modulation scheme based on orthogonal space-time block coded - Zhi-cheng WANG; Zhi-gang CHEN; Lei WANG (Tongxin xuebao)
Focusing on the problem that differential spatial modulation (DSM) couldn’t obtain transmit diversity and has high decoding complexity,a new differential spatial modulation scheme based on the orthogonal space-time block code was proposed and the proposed scheme is called OSTBC-DSM.There were two matrices in this scheme:the spatial modulation matrix and the symbol matrix.The former was aimed to activate different transmit antennas by setting the position of nonzero elements,and the latter structured symbolic matrix by using orthogonal space-time block codes (OSTBC) as the basic code block.The proposed scheme could obtain full transmit diversity and higher spectral efficiency compared with the conventional DSM schemes.Moreover,the OSTBC-DSM supported linear maximum likelihood (ML) decoding.The simulation results show that under different spectral efficiencies,the proposed OSTBC-DSM scheme has better bit error rate (BER) performance than other schemes.